Effects of incubation conditions on nutrient mineralisation rates in fish and shrimp. (10th May 2018) - Oliveira‐Cunha, Priscila; Capps, Krista A.; Neres‐Lima, Vinicius; Lourenço‐Amorim, Christine; Tromboni, Flavia; Moulton, Timothy P.; Zandonà, Eugenia
Abstract: Consumer mineralisation of nutrients can affect ecosystem processes, such as primary productivity, community respiration and biogeochemical cycling. Researchers have not tested, however, the influence of standard incubation methods on mineralisation rates. Therefore, the influence of varied incubation methods on consumer mineralisation rates is poorly understood. Here, we investigated how incubation conditions affected the mineralisation rates of ammonium and phosphate of two species of fish and two species of shrimp. For each species, we measured mineralisation rates during the day and at night in two incubation environments (standard and modified to reduce stress). We also estimated the effect of conspecific density (1, 3 or 5 individuals) and the duration of incubation (after 15, 30, 45, 60 and 75 min) on mineralisation for a species of shrimp. Our results indicated mass‐specific N mineralisation by three species was influenced by the time of day, and for two of the species, mass‐specific N mineralisation was also influenced by incubation conditions. Mass‐specific mineralisation rates for both N and P by a species of shrimp decreased significantly with increasing incubation time, but we did not detect significant differences in mineralisation among incubation durations or densities for either element. Mass‐specific mineralisation rates for P were negatively correlated with body size for all studied species, as previously reported. Only the two species of shrimp showed the expected negative relationship between mass‐specific N mineralisation rates and body size. Our results suggest that the mechanisms by which organisms excrete elements are differentially influenced by incubation conditions. Our study highlights the need to develop methods specific to the organisms of interest, especially the duration and the time of day of the incubation. Additionally, our attempt to influence mineralisation rates by modifying chamber design was mostly ineffective, indicating that this measure may not be a priority for future studies.